STUDENTS’ MATHEMATICS LEARNING DIFFICULTIES IN TERMS OF METACOGNITIVE ABILITY: A SYSTEMATIC LITERATURE REVIEW - Husnul Khatimah Rusyid; Dadang Juandi (Pedagogy: Jurnal Pendidikan Matematika, 2023)
Mathematics learning difficulties are an important aspect to be addressed in learning. By developing students' metacognition skills, learning difficulties can be minimized. Many studies have been conducted related to students' mathematics learning difficulties in terms of metacognition abilities. The purpose of this study is to determine the heterogeneity of research based on the year of publication, level of education, research methods used, demographics of the research country, and the type of learning difficulties experienced by students seen from the indicators of metacognition ability. The method used in this research is Systematic Literature Review (SLR) based on a quantitative descriptive approach using the PRISMA protocol. The results showed that the analysis of students' mathematics learning difficulties in terms of metacognition ability was most widely published in 2021 at the junior high school level. Indonesia dominates research with similar topics and uses qualitative research methods. Most of the mathematics learning difficulties experienced by students are seen from the classification of metacognition ability categories, namely classifying objects based on the requirements for forming concepts, identifying the properties of operations or mathematical concepts and symbols.